Resenha do livro: "Cyber War: the next threat to national security and what to do about it" - Canabarro, Diego Rafael (Conjuntura Austral, 2011)
Resenha de CLARKE, Richard A; KNAKE, Robert K. (2010). Cyber War: The Next Threat to National Security and What To Do About It. Nova Iorque: HarperCollins, 290 p. [ISBN: 978-0-06-196223-3]